Report to the community : Highlights from 2019-2021 and overview of where we’re headed - Jeffery Hale - Saint Brigid's (JHSB) (2021)
Number of pages: 10

Rapport à la communauté : Faits saillants de 2019-2021 et aperçu de nos orientations - Jeffery Hale - Saint Brigid's (JHSB) (2021)
Number of pages: 10

Report to the Community : Highlights from 2018-2019 and Overview of Where We're Headed - Jeffery Hale - Saint Brigid's (JHSB) (2019)
Number of pages: 8

In Touch - Jeffery Hale - Saint Brigid's (JHSB) (2016)
Number of pages: 2

Recovery Support Program : A Community Wellness Program for English-speaking People with Mental Illness - Jeffery Hale - Saint Brigid's (JHSB) (2014)

Fall Prevention : Information for Clients and Their Families - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Infection Control : Important Facts for Families, Volunteers and Visitors - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Influenza : You Can Help Prevent and Control the Flu / Influenza : Vous pouvez aider à prévenir et contrôler la grippe - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Preventing Pressure Sores : A Guide for Clients and Their Families / Prévention des plaies de pression : Un guide à l'intention des patients et de leurs familles - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Restraints : Information for Clients and Families / Mesures de contrôle : Publications aux usagers et aux proches - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Roles and Responsibilities in Patient Safety : Physicians, Staff and Volunteers / Rôle et responsabilités dans la securité des patients : Médecins, personnel et bénévoles - Jeffery Hale - Saint Brigid's (JHSB) (2013)

[Jeffery Hale Residents' Committee List / Jeffery Hale comité des résidents liste de membres] - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Saint Brigid's Residents' Committee / Saint Brigid's comité des résidents - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Composition du Comité des usagers du Jeffery Hale - Saint Brigid's - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Plan de sécurite des usagers - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Comité des résidants Jeffery Hale : Nous vous souhaitons la bievenue chez-vous - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Saint Brigid's Residents' Committee : Welcome to Your Home! / Saint Brigid's Comité des résidents : Bienvenu(e) chez vous ! - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Service Offer : Jeffery Hale Community Services - Jeffery Hale - Saint Brigid's (JHSB) (2010)
Jeffery Hale Community Services (JHCS) has a delegated responsibility to offer primary, CLSC type services to the English-speaking population in the CNR, as well as support a coordinated, consolidated service offer for this community. Through alliances with community partners, we work on ensuring the development and vitality of the English-speaking community. JHCS provide youth and family services, mental health programs, and for seniors, home care and a day centre.

Public Health Action Plan for the English-Speaking Community in the Capitale-Nationale Region 2011-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2011)
Saint Brigid’s – Jeffery Hale Hospital’s Public Health Action Plan for the English- Speaking Community in the Capitale-Nationale Region is in keeping with the Plan d’action regional (PAR) en santé publique 2009-2012 (regional public health action plan) developed by the Agence de la santé et des services sociaux de la Capitale-Nationale (Agence). To ensure viable results for our efforts aimed at improving the health and well-being of the English-speaking community, we thought it relevant to begin by presenting an updated portrait of the English-speaking community in the CNR. This portrait allows us to identify the various needs of the community, as well as its health determinants and indicators, and take stock of its ongoing evolution. This description is followed by a detailed presentation of Saint Brigid’s – Jeffery Hale Hospital’s prevention and health promotion Service Offer.

Priorités d'action 2013-2014 : Document global - Jeffery Hale - Saint Brigid's (JHSB) (2013)
Issu de la communauté d’expression anglaise de la grande région de Québec et investi de sa longue tradition d’entraide, l’Hôpital Jeffery Hale – Saint Brigid’s est un établissement public bilingue sous gouvernance participative, engagé à offrir des services sécuritaires de la plus haute qualité empreints de compassion. Il contribue concrètement à la santé et au bien-être de la population de la région en collaboration avec ses partenaires du réseau de la santé et des services sociaux et de la communauté à travers ses services communautaires et généraux de première ligne pour tous les groupes d’âges de même que ses services variés destinés aux personnes en perte d’autonomie. L’Hôpital Jeffery Hale – Saint Brigid’s joue un rôle central de soutien à la communauté d’expression anglaise et à sa vitalité. Il assume le leadership d’actions concertées visant à contribuer au développement de cette communauté et à la santé et au bien-être de ses membres.

Planification stratégique : 2012-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2012)
Le présent document est le résultat d’une démarche entreprise par le conseil d’administration de l’Hôpital Jeffery Hale – Saint Brigid’s, il y a plus d’un an. À la suite de multiples consultations auprès de nos instances internes et externes, le conseil a élaboré les orientations stratégiques sur lesquelles nous fonderons nos actions pour les prochaines années. Elles sont présentées à nos partenaires externes suite à son adoption au printemps 2012.

Règlement : Procédure d'examen des plaintes - Jeffery Hale - Saint Brigid's (JHSB) (2013)
Ce règlement sur la procédure d’examen des plaintes des usagers de l’Hôpital Jeffery Hale - Saint Brigid’s a été élaboré à partir d’un projet-type de règlement élaboré par l’Association québécoise d’établissements de santé et de services sociaux du Québec, notamment par Me Sonia Amziane, avocate-conseil à l’AQESSS, avec la collaboration de Me Sylvain Poirier du cabinet de Heenan Blaikie, dans le contexte de l’entrée en vigueur de la Loi modifiant la Loi sur les services de santé et les services sociaux et d’autres dispositions législatives (L.Q. 2005, c. 32) (projet de loi no 83).

Strategic Plan 2012 - 2015 : Summary Document - Jeffery Hale - Saint Brigid's (JHSB) (2013)

[Complaint or Positive Comment Form / Formulaire de plainte ou commentaire positif] - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Disclosure : Your Right to be Informed / Divulgation : Le droit d'être informé - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Composition du comité consultatif du Jeffery Hale – Saint Brigid’s: Mandat 3 ans : 2015-2018 - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

[Jeffrey Hale - Saint Brigid's Users' Committee : Rapport annuel 2020-2021] - Jeffery Hale – Saint Brigid’s (JHSB) Users' Committee (2021)

Users and Residents : Have Your Say / Usagers et résidents : La parole est à vous - Jeffery Hale – Saint Brigid’s (JHSB) Users' Committee

[Hôpital Jeffery Hale-Saint Brigid's agréé avec mention d'honneur] - Larocque, Suzanne (2013)